Employee Productivity Determination: In Work Life Balance (WLB), Work From Home (WFH), Information Technology (IT) and Work Flexibility - Suryadi, Yohanes; FoEh, John E.H.J; Manafe, Henny (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
This article reviews the factors that affect the productivity of employee work, namely: Work-Life Balance (WLB) which is used as a mediating variable, Work From Home (WFH), Information Technology (IT), and Work Flexibility. The study is literature review research. The literature review is a comprehensive summary of previous research on a topic. According to the theory, the appropriate article and its discussion can be seen that some studies support the thought of the research hypothesis of this study while some do not. From the hypothesis determined, there is no research conducted to determine whether WFH, IT, and WLB together can affect work productivity through WLB. Therefore, future research especially quantitative research needs to be conducted to prove the theory.